The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.jtcvs.2012.03.078
|View full text |Cite
|
Sign up to set email alerts
|

Unplanned reinterventions are associated with postoperative mortality in neonates with critical congenital heart disease

Abstract: Objective Neonates with critical congenital heart disease remain at risk of adverse outcomes after cardiac surgery. Residual or undiagnosed anatomic lesions might be contributory. The present study aimed to describe the incidence and type of cardiac lesions that lead to early, unplanned cardiac reintervention, identify the risk factors for unplanned reintervention, and explore the associations between unplanned reinterventions and hospital mortality. Methods The present single-center retrospective cohort stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 19 publications
(27 reference statements)
3
29
1
Order By: Relevance
“…In addition, it helps the providers and the family to plan and coordinate an effective multidisciplinary care of these patients, well in advance of the delivery of the child . However, the benefits of prenatal diagnosis on morbidity and mortality in these infants are still a subject of debate . In this study, we found that prenatal diagnosis of complex CHD significantly improves the preoperative morbidity, more so with ductal‐dependent cardiac lesions (Table ).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In addition, it helps the providers and the family to plan and coordinate an effective multidisciplinary care of these patients, well in advance of the delivery of the child . However, the benefits of prenatal diagnosis on morbidity and mortality in these infants are still a subject of debate . In this study, we found that prenatal diagnosis of complex CHD significantly improves the preoperative morbidity, more so with ductal‐dependent cardiac lesions (Table ).…”
Section: Discussionmentioning
confidence: 69%
“…Our results were similar to the findings in this study. In fact, some studies have even shown that prenatal diagnosis was associated with worse postoperative outcomes . The authors in those studies have hypothesized that postoperative outcomes are primarily influenced by the severity of the cardiac malformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Important post‐surgical anastomotic narrowings, ranging from mild stenosis to outright complete obstruction, can result in hemodynamic instability in the early post‐operative period. In order to address such stenotic lesions, these patients often require an early reoperation, which can be associated with major risks including hemodynamic instability, delayed recovery, and even mortality . However, in many cases the stenotic lesions can be addressed safely in the catheterization laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the trainee should be able to recognize patients who have a residual cardiac lesion, either due to an imperfect operation or incomplete preoperative diagnosis, and plan appropriate anatomic investigation and determine the need to recommend surgical or transcatheter intervention when clinically indicated. 3 In particular, the trainee should have sufficient training and experience to be effective in managing these types of patients:…”
Section: Interpersonal and Communication Skillsmentioning
confidence: 99%